2014
DOI: 10.18052/www.scipress.com/ilshs.43.152
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Performance: The Role of Transparency & Disclosure in Banking Sector of Pakistan

Abstract: Purpose: This purpose of this paper is to empirically examine the relationship between transparency and disclosure and firm performance. Highlighting the importance of corporate governance in banking sector, the paper has focused in depth over its role, level and its impact on performance in banking industry of Pakistan. Design/methodology/approach: The paper access this purpose by constructing transparency and disclosure index for the past five year 2007-2011, using proxies for three sub-categories which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…As for transparency and disclosure index, Table 4 shows that TDI insignificantly affects ROA in the case of India, the Gulf countries and collective model. This result is inconsistent with the studies performed by Sharif and Ming Lai (2015) and Zaman et al (2015) who argue that TDI significantly impacts firms' performance measured by ROA. On the contrary, this finding is in line with the study performed by Hassan (2012) who found that TDI insignificantly impacts the ROA.…”
Section: Results Of Model One: Return On Assetscontrasting
confidence: 96%
“…As for transparency and disclosure index, Table 4 shows that TDI insignificantly affects ROA in the case of India, the Gulf countries and collective model. This result is inconsistent with the studies performed by Sharif and Ming Lai (2015) and Zaman et al (2015) who argue that TDI significantly impacts firms' performance measured by ROA. On the contrary, this finding is in line with the study performed by Hassan (2012) who found that TDI insignificantly impacts the ROA.…”
Section: Results Of Model One: Return On Assetscontrasting
confidence: 96%
“…Corporate transparency and disclosure is an element to gain stakeholders’ trust among companies (Barako et al , 2006). Furthermore, it is a well-established fact that high quality corporate transparency and disclosure reduce the information asymmetries, increase stakeholder trust – and are associated with positive capital market consequences such as lower cost of capital (Qian et al , 2015), increase in shareholders’ value (Aksu and Kosedag, 2006), better firm performance and competitive advantage (Aksu and Kosedag, 2006; Zaman et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In developed markets, mature business ethics motivates companies to actively engage in corporate disclosure (Kavitha and Anita, 2011; Zhang et al , 2010). However, it is under research in emerging markets, especially in Pakistan, whether these media coverages influence governance practices for transparency and disclosure, where business ethics are immature, information transparency and disclosure are not well articulated and the CG infrastructure is weak (Zaman et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Assets represent the economic resources owned by an entity, tangible or intangible that are available for use for the purpose of generating revenue now or in the future (Saigeetha & Surulivel, 2017). While total assets depict the total value of all resources in monetary terms that belong to an organization, non-current assets are assets that have the features of lasting beyond one accounting period (Muhammad, 2015). According to Divya, Simram and Vartika (2017), every organization is likely to operate with current and non-current assets in its normal business engagements.…”
Section: Non-current Assetsmentioning
confidence: 99%